Proteolytic Hydrolysis of Rice (Oryza Sativa Basmati) - Ong, Lisa Gaik Ai (2001)
Protein hydrolysate has been produced a long time ago. It is normally use as animal feed or as a substitute for dietary patient and the protein used is usually obtained from seafood. In this study, we are more interested in the production of protein hydrolysate from rice. The rice that was used in this study were obtained form BERNAS, Padi National Bhd, and it was pretreated by first grinding it into fine powder, prior to analysis. The rice flour was found to consist of 11.77% of moisture, 0.46% of ash and 5.79% of crude protein. The commercial enzyme that was used for this study were Flavourzyme, Alcalase (Novo Nordisk, Denmark) and Papain (Sigma, USA). The enzyme activities and the stability of the enzymes were determined first before they were used for the "production of protein hydrolysate. From the enzyme decay experiment, three of the enzymes were found to be stable at 55°C. Flavourzyme was totally denatured at 100°C, but for Alcalase (0.624%) and Papain (2.104%), some activity was still detected. Therefore, Alcalase and Papain can be clarified as being thermostable. Papain was used as comparison with Flavourzyme and Alcalase, to determine which enzyme performed better in producing the hydrolysates. From the correlation between the free amino group, Flavourzyme ( R2 value is 0.9291) and Alcalase ( R2 value is 0.6719) were found to have a better correlation and they give a higher degree of hydrolysis compared with Papain ( R2 value is 0.5152). Therefore, Flavourzyme and Alcalase were selected for further study. The protein hydrolysate that was produced from Flavourzyme and Alcalase gave lower molecular weight subunits, which was 342 Da and 161.46 Da, respectively as detected by size exclusion high performance liquid chromatography. The free amino acids that were present in the hydrolysate were hydrolysed by the commercial enzymes and detected using the PICO-Tag method. From the kinetic analysis, Alcalase was found to form enzyme-substrate complex easier compared to Flavourzyme. However, the production rate for Alcalase was lower compared with Flavourzyme, which was 8.14 for Alcalase and 34.80 for Flavourzyme using Eadie-Hofstee equation.